Estudio de caso para la delimitación y diagnóstico de áreas de protección de captación para el abastecimiento público en el Sistema Acuífero Guaraní (Journal on studies and research of academic knowledge, 2015)
It was carried out a spatial analysis using hydro geological information and field observation to define and diagnose minimum protection areas of water sources for human consumption. Preliminarily, GOD methodology was used to determine groundwater vulnerability. Furthermore, as a main procedure, fixed radio calculations were used for 24 hours and 50 days as well as Wyssling methodology to determine protection areas. The results indicate that there is a conflict of the defined protection areas and the activities currently taking place within, also supported by water quality analysis carried out by third authors which indicate contamination in the area (Phosporus and E. Coli). The information generated from our work represents concrete recommendations directed to the management of the protection areas supported by biophysical data, indicating the need for actions to be taken to stop degradation of water quality of the aquifer and reduce the possible negative effects on the inhabitants of the region.
Keywords: Paraguay; Guarani Aquifer System; Vulnerability